-3(4t-3)+5t=6t-5

Simple and best practice solution for -3(4t-3)+5t=6t-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(4t-3)+5t=6t-5 equation:


Simplifying
-3(4t + -3) + 5t = 6t + -5

Reorder the terms:
-3(-3 + 4t) + 5t = 6t + -5
(-3 * -3 + 4t * -3) + 5t = 6t + -5
(9 + -12t) + 5t = 6t + -5

Combine like terms: -12t + 5t = -7t
9 + -7t = 6t + -5

Reorder the terms:
9 + -7t = -5 + 6t

Solving
9 + -7t = -5 + 6t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-6t' to each side of the equation.
9 + -7t + -6t = -5 + 6t + -6t

Combine like terms: -7t + -6t = -13t
9 + -13t = -5 + 6t + -6t

Combine like terms: 6t + -6t = 0
9 + -13t = -5 + 0
9 + -13t = -5

Add '-9' to each side of the equation.
9 + -9 + -13t = -5 + -9

Combine like terms: 9 + -9 = 0
0 + -13t = -5 + -9
-13t = -5 + -9

Combine like terms: -5 + -9 = -14
-13t = -14

Divide each side by '-13'.
t = 1.076923077

Simplifying
t = 1.076923077

See similar equations:

| 48+x(9+3)=288 | | 7u+5=5 | | -4v+8(v+2)=-4 | | 8g-7=-39 | | 3y+2f-f+1-3y+7=32 | | 2k+5=3 | | -5n+3=-4n-4 | | -6=-6w+4(w+3) | | 4b^2-169y^2= | | 9x+3x=10101010101001101 | | c+bc-11c-4=13c+4-2 | | 2k+10=k+15 | | (8/t-7)-3/t | | 15=2a-2 | | 18+6x+x^2=0 | | 5x-5y=10z | | -4/35/8/7 | | 2(4x+8)=x+7x-2 | | -7=-7x+3(x+5) | | -a+2a=4a+6-2 | | -3y=6/5 | | -4x/7=-12 | | 6x=-6x+144 | | 6x-15=5x-9 | | 5/-5 | | x-3/x= | | 6x/39 | | -5/9w=35 | | 44.95(t-25)=2511.6 | | (a+3b)+(3a-b)i=6+6i | | x×x-3/x= | | x×x-3/x=18 |

Equations solver categories